THE EFFECT OF INTERNAL CORPORATE SOCIAL RESPONSIBILITY ON EMPLOYEE PERFORMANCE AT PT. PERTAMINA GEOTHERMAL ENERGY AREA LAHENDONG - Liany Elfirany Senduk; David P. E. Saerang; Shinta J. C. Wangke (Universitas Sam Ratulangi, 2024)
The idea that a firm’s single purpose is to make profits has dictate the way business are conducted by most organizations, leading to a mindset focus on short term results, with less attention given to most business stakeholders. This study aims to prove that the internal corporate social responsibility affected the employee performance at PT. Pertamina Geothermal Energy Area Lahendong. Internal CSR in this research represented by three dimension namely work-life balance (x1), skill development (x2), and workforce diversity (x3) as independent variable while employee performance (y) as the dependent variable. Researcher use the quantitative methods by distributing questionnaires through 69 respondents as the research sample and processed the data through multiple linear regression analysis. The result of this study shows that work-life balance, skill development, and workforce diversity have a positive and significant effect on employee performance. Keyword: Internal Corporate Social Responsibility, Work-Life Balance, Skill Development, Workfoce Diversity, Employee Performance